Adhesion properties of cell surface proteins in Lactobacillus strains in the GIT environment. Issue 6 (28th February 2022) - Yu, Yixing; Zong, Manli; Lao, Lifeng; Wen, Jianzhu; Pan, Daodong; Wu, Zhen
Abstract : Surface molecules of the Lactobacillus strains are related to the adhesion property and this property are enhanced upon the external environmental stress, such as temperature, pH, sub-strength and ion concentration through the Quorum sensing effect. Abstract : As a broadly defined member of lactic acid bacteria (LAB), the Lactobacillus strain is well characterized in food fermentation and specific strains can enhance the intestinal barrier function and be recognized as the probiotic strain. In recent years, many molecules of the cell surface are thought to be related to the adhesion property in the gastrointestinal mucosa. Mucus layer-related proteins, extracellular matrix proteins, and immunoglobulins also exhibit immunity regulation and protection of the intestinal epithelial barrier function. Meanwhile, the effects of bile and the low pH of the gastrointestinal tract (GIT) on Lactobacillus colonization are also needed to be considered. Furthermore, LAB can adhere and aggregate in the GIT to promote the maturity of biofilm and the extracellular matrix secreting through the signal molecules in the quorum sensing (QS) system. Therefore, it is of great interest to use the QS system to regulate the initial adhesion ability of Lactobacillus and further enhance the probiotic effect of the biofilm formation of beneficial bacteria. This review summarizes the adhesion properties of cell surface proteins derived from Lactobacillus strains in recent studies and provides valuable information on the QS effect on the adhesion property of Lactobacillus strains in the GIT environment.